Feasibility Study of Using Blockchain Technology for Criminal Records in Central Java - Wulan, Puspa Ira Dewi Candra; Fauzi, Rofiq; Perdana, Danis Putra; Alfianto, Muhamad Eko; Maharani, Clarissa Monique; Abdi Susila, Yudha Satria (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2024)
A criminal record is an official document filed with the police that contains a person's criminal history. In practice, managing criminal record data is not easy, the complex challenge is the risk of data manipulation. Data manipulation is carried out for various purposes, one of which is deleting or changing data for certain purposes. The increase in cyber crime in Indonesia does not rule out the possibility that criminal record data will be hacked. Blockchain technology, through smart contracts, is an innovative solution to overcome the problem of data manipulation. Blockchain as an immutable distributed digital ledger, provides guarantees of data security and integrity. By adopting smart contracts in data collection, it can increase the speed of information access, reduce the risk of manipulation and provide a high level of transparency. A feasibility study regarding the importance of implementing Blockchain technology for storing criminal records needs to be carried out before deciding to realize this technology.  The aim of this research is to analyze how important it is that criminal record data must be secured using Blockchain technology in Central Java.  Qualitative methods were used in this research, data collection was carried out using interview techniques with predetermined sources